Varying effects of Vicia sativa and Vicia villosa on bacterial composition and enzyme activities in nutrient-deficient sugarcane soils under greenhouse conditions - Emihle Ngonini; María A. Pérez-Fernández; Anathi Magadlela (Scientific Reports)
Abstract Declining soil health and productivity are key challenges faced by sugarcane small-scale growers in South Africa. Incorporating Vicia sativa and Vicia villosa as cover crops can improve soil health by enhancing nutrient-cycling enzyme activities and nitrogen (N) contributions while promoting the presence of beneficial bacteria in the rhizosphere. A greenhouse experiment was conducted to evaluate the chemical and biological inputs of V. sativa and V. villosa in nutrient-deficient, KwaZulu-Natal (KZN) sugarcane plantation soils. The nutrient concentrations, N and phosphorus (P) cycling bacteria, and extracellular enzyme activities of 5 soils were determined pre-planting and post-V. sativa and V. villosa harvest. Post-harvesting soils had higher pH levels than pre-planting soils. The number of plant growth-promoting rhizobacteria increased post-V. sativa and V. villosa harvest, with Arthrobacter, Burkholderia, Paraburkholderia and Pseudomonas as the dominant genera. Acid phosphatase and glucosidase activities increased, with Mvutshini and Mzinto showing the most significant increases (phosphatase: 18.66 to 84.67 for V. villosa, 90.33 for V. sativa; glucosidase: 15.33 to 83 for V. villosa and 105 µmolh− 1g− 1 for V. sativa). In conclusion, V. sativa and V. villosa increased PGPR, pH and enzyme activities, making them viable cover crops for nutrient-deficient sugarcane soils.